A comparison of 2‐hydroxyglutarate detection at 3 and 7 T with long‐TE semi‐LASER. (5th January 2018) - Berrington, Adam; Voets, Natalie L.; Larkin, Sarah J.; de Pennington, Nick; Mccullagh, James; Stacey, Richard; Schofield, Christopher J.; Jezzard, Peter; Clare, Stuart; Cadoux‐Hudson, Tom; Plaha, Puneet; Ansorge, Olaf; et al.
Abstract : Abnormally high levels of the 'oncometabolite' 2‐hydroxyglutarate (2‐HG) occur in many grade II and III gliomas, and correlate with mutations in the genes of isocitrate dehydrogenase (IDH) isoforms. In vivo measurement of 2‐HG in patients, using magnetic resonance spectroscopy (MRS), has largely been carried out at 3 T, yet signal overlap continues to pose a challenge for 2‐HG detection. To combat this, several groups have proposed MRS methods at ultra‐high field (≥7 T) where theoretical increases in signal‐to‐noise ratio and spectral resolution could improve 2‐HG detection. Long echo time (long‐TE) semi‐localization by adiabatic selective refocusing (semi‐LASER) (TE = 110 ms) is a promising method for improved 2‐HG detection in vivo at either 3 or 7 T owing to the use of broad‐band adiabatic localization. Using previously published semi‐LASER methods at 3 and 7 T, this study directly compares the detectability of 2‐HG in phantoms and in vivo across nine patients. Cramér–Rao lower bounds (CRLBs) of 2‐HG fitting were found to be significantly lower at 7 T (6 ± 2%) relative to 3 T (15 ± 7%) ( p = 0.0019), yet were larger at 7 T in an IDH wild‐type patient. Although no increase in SNR was detected at 7 T (77 ± 26) relative to 3 T (77 ± 30), the detection of 2‐HG was greatly enhanced through an improved spectral profile and increased resolution at 7 T. 7 T had a large effect on pairwise fitting correlations between γ‐aminobutyric acid (GABA) and 2‐HG ( p = 0.004), and resulted in smaller coefficients. The increased sensitivity for 2‐HG detection using long‐TE acquisition at 7 T may allow for more rapid estimation of 2‐HG (within a few spectral averages) together with other associated metabolic markers in glioma. Abstract : Long‐echo time (long‐TE) magnetic resonance spectroscopy (MRS) has been proposed to be useful for the measurement of the biomarker 2‐hydroxyglutarate (2‐HG) in patients with glioma. In this study, a comparison using semi‐localization by adiabatic selective refocusing (semi‐LASER) (TE = 110 ms) at 3 T and 7 T reveals significantly improved 2‐HG Cramér–Rao lower bounds (CRLBs) in patients with glioma, together with improvement in the pairwise fitting correlation with γ‐aminobutyric acid (GABA) at 7 T. The superior spectral profile at 7 T allowed for the detection (CRLB < 20%) of 2‐HG after two acquired transients compared with 64 at 3 T.